2010
DOI: 10.1523/jneurosci.2481-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Mental Hoop Diaries: Emotional Memories of a College Basketball Game in Rival Fans

Abstract: The rivalry between the men’s basketball teams of Duke University and the University of North Carolina-Chapel Hill (UNC) is one of the most storied traditions in college sports. A subculture of students at each university form social bonds with fellow fans, develop expertise in college basketball rules, team statistics, and individual players, and self-identify as a member of a fan group. The present study capitalized on the high personal investment of these fans and the strong affective tenor of a Duke-UNC ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 48 publications
4
38
0
4
Order By: Relevance
“…Botzung, Rubin, Miles, Cabeza, and LaBar (2010) also found a right-hemispheric amygdalar activation during the retrieval of highly emotional memories. In patients with dissociative amnesia -a condition that is accompanied by a failure of integration of emotive with memory processing functions -we found evidence for right hemispheric dysfunction, such as a hypometabolism of the right inferior lateral prefrontal cortex (Brand et al, 2009).…”
Section: Eam and The Brainmentioning
confidence: 76%
“…Botzung, Rubin, Miles, Cabeza, and LaBar (2010) also found a right-hemispheric amygdalar activation during the retrieval of highly emotional memories. In patients with dissociative amnesia -a condition that is accompanied by a failure of integration of emotive with memory processing functions -we found evidence for right hemispheric dysfunction, such as a hypometabolism of the right inferior lateral prefrontal cortex (Brand et al, 2009).…”
Section: Eam and The Brainmentioning
confidence: 76%
“…Increased activations in healthy controls were also observed in the somatosensory regions during the elaboration phase (vs. the construction phase), not evident in the patient group. In the AM literature, the somatosensory cortex is closely linked to the retrieval of somatosensory representations related to the event, the emotional intensity, and is also especially engaged during the elaboration of events (Daselaar et al 2008;Botzung et al 2010). …”
Section: Fig 4 Significant Brain Activations For the Group X Task Inmentioning
confidence: 99%
“…Recent neuroimaging evidence also suggests that AMY plays a role in the successful retrieval of personally relevant events following shorter retention intervals. By investigating basketball fans' memories for specific basketball games, encoded a few days before the scanning session, Botzung, Rubin, Miles, Cabeza, and Labar (2010) showed that AMY activity was modulated by the emotional intensity of the recollected events, and was greater for extremely high-vs. low-intensity events . Hence, this study also points to the involvement of AMY in the retrieval of emotional, personally relevant, events (see also Muscatell, Addis, & Kensinger, 2010;Sharot, Martorella, Delgado, & Phelps, 2007).…”
Section: Neural Correlates Of the Memory-enhancing Effect Of Emotion mentioning
confidence: 99%